De platano - Hahn, Petrus Olai; Lönwall, Johannes Sunonis; Wall, Johan Larsson; Kungliga akademin i Åbo; Royal Academy in Turku; Regia Academia Aboensis; Kuninkaallinen Turun akatemia ([Aboae] : impr. apud Jo. Wallium, [1695], 1695)
Invocatio: Q.F.F.Q.S.
Keywords: kasvitiede